Young British Muslims : Identity, Culture, Politics and the Media. - Kabir, Nahid Afrose (Edinburgh University Press, 2010)
In Britain's highly politicised social climate in the aftermath of the 7/7 London bombings, Young British Muslims: Identity, Culture, Politics and the Media provides an in-depth understanding of British Muslim identity through the following social constructs: migration history, family settlement, socio-economic status, religion and culture, and the wider societal environment. The author, Nahid Afrose Kabir, has carried out extensive research on young Muslims' identity in Australia and the UK. For this book she conducted ethnographic fieldwork in the form of in-depth, semi-structured interviews of over 200 young Muslims in five British cities: London, Leicester, Bradford, Leeds and Cardiff. Kabir's careful analysis of interview responses offers insights into the hopes and aspirations of British Muslims from remarkably diverse ethnicities: Algerian, Bangladeshi, Egyptian, Indian, Iranian, Iraqi, Kenyan, Lebanese, Libyan, Malawi, Mauritian, Moroccan, Nigerian, Pakistani, Palestinian, Singaporean, Somali, Sudanese, Syrian, Ugandan, Yemeni, and English, Danish and Scottish converts. By emphasising the importance of biculturalism, the author conveys a realistic and hopeful vision for their successful integration into British society. Nahid Afrose Kabir is a visiting fellow at the Center for Middle Eastern Studies at the Harvard University, USA. She is the author of Muslims in Australia: Immigration, Race Relations and Cultural History (2005).